2016
DOI: 10.1007/s00299-016-2049-0
|View full text |Cite|
|
Sign up to set email alerts
|

Physiological differences and changes in global DNA methylation levels in Agave angustifolia Haw. albino variant somaclones during the micropropagation process

Abstract: Global DNA methylation changes caused by in vitro conditions are associated with the subculturing and phenotypic variation in Agave angustifolia Haw. While the relationship between the development of albinism and in vitro culture is well documented, the role of epigenetic processes in this development leaves some important questions unanswered. During the micropropagation of Agave angustifolia Haw., we found three different phenotypes, green (G), variegated (V) and albino (A). To understand the physiological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 74 publications
0
24
1
Order By: Relevance
“…Abnormalities in plantlets induced by epigenetic factors have been reported in different crops (Kitimu et al 2015;Ghosh et al 2017;Goyali et al 2018). In Agave angustifolia Haw., albinism was related to the tissue culture environment where the missing of color in leaves was correlated with high levels of DNA methylation (Duarte-Aké et al 2016). In Elaeis guineensis Jacq.…”
Section: Crop Specie Somaclonal Variation Type Causes Of Variation/anmentioning
confidence: 99%
“…Abnormalities in plantlets induced by epigenetic factors have been reported in different crops (Kitimu et al 2015;Ghosh et al 2017;Goyali et al 2018). In Agave angustifolia Haw., albinism was related to the tissue culture environment where the missing of color in leaves was correlated with high levels of DNA methylation (Duarte-Aké et al 2016). In Elaeis guineensis Jacq.…”
Section: Crop Specie Somaclonal Variation Type Causes Of Variation/anmentioning
confidence: 99%
“…Albino plantlet regeneration is associated with aberrant plastid formation and plastidic DNA deletions [74,75], altered expression of photosynthesis, porphyrin and chlorophyll metabolism genes [67], global DNA methylation changes [76], and modified physiology [76,77]. Furthermore, QTL studies have identified 14 chromosome regions associated with albinism in triticale [78], which suggested a role for oxidative stress during the proplastid to functional chloroplast transition in the promotion of albinism during in vitro regeneration.…”
Section: Albino Regenerationmentioning
confidence: 99%
“…Albino plantlet regeneration is associated with aberrant plastid formation and plastidic DNA deletions (Day and Ellis 1984, Dunford and Walden 1991), altered expression of photosynthesis, porphyrin and chlorophyll metabolism genes (Zhao et al 2017), global DNA methylation changes (Duarte-Aké et al 2016), and modified physiology (Duarte-Aké et al 2016; Isah 2019). Furthermore, QTL studies have identified 14 chromosome regions associated with albinism in triticale (Krzewska et al 2015), which suggested a role for oxidative stress during the proplastid to functional chloroplast transition in the promotion of albinism during in vitro regeneration.…”
Section: Discussionmentioning
confidence: 99%